Perfil y Tipología del Cuestionario de Eficacia Colectiva para el Deporte (CEQS) en Colombia - Ladrón, Amalia Gissell; Millán, Anthony Constant; Gómez, John Anibal; Trabucco, Juan Carlos; D’Aubeterre, María Eugenia (Pontificia Universidad Católica del Perú, 2022)
The factorial structure, the psychometric properties and the norms of interpretation and correction of the profile, and the typology of the adaptation to Spanish of the Collective Efficacy Questionnaire for Sport (CEQS) by Martínez, Guillén & Feltz (2011) are examined, in a sample of Colombian athletes, because in their previous validations no strategies were applied to minimize the bias from factorial indeterminacy, confirmatory and by capitalization on the chance. Contrary to the CEQS five-factors structure originally postulated by Martínez et al. (2011), findings in this study show a two-factor structure. Convergent validity shows that the two factors predict the quality of the players' relationship. Finally, no differences were found in the scores of the two CEQS factors associated with sociodemographic or socio-sports variables. Recommendations are presented on the use and interpretation of this instrument by experts in sport psychology, coaches, and sports administrators, and the contribution of the implementation of the CEQS to the improvement of effectiveness in team sports.

Se examina la estructura factorial, las propiedades psicométricas y las normas de interpretación y corrección del perfil y la tipología de la adaptación al español del Cuestionario de Eficacia Colectiva para el Deporte (CEQS) de Martínez, Guillén y Feltz (2011), en una muestra de deportistas colombianos, debido a que en sus validaciones previas no se aplicaron estrategias para minimizar el sesgo de indeterminación factorial, confirmatorio y de capitalización del azar. Se encontró una estructura de 2 factores, diferente a la de 5 que originalmente postularon Martínez y col. (2011). La validez convergente muestra que los dos factores predicen la calidad de la relación de los jugadores. Finalmente, no se encontraron diferencias en los puntajes de los dos factores del CEQS asociados a variables sociodemográficas ni sociodeportivas. Se presentan recomendaciones sobre la utilización e interpretación de este instrumento por parte de los expertos en psicología del deporte, entrenadores y administradores deportivos y la contribución de la implementación del CEQS a la mejora de la eficacia en deportes de equipo.

On examine, dans un échantillon d'athlètes colombiens, car dans leurs validations précédentes aucune stratégie n'a été appliquée pour minimiser le biais d'indétermination factorielle, de confirmation et de capitalisation sur le hasard. Contrairement à la structure à cinq facteurs du CEQS initialement postulée par Martínez et al. (2011), les résultats de cette étude montrent une structure à deux facteurs. La validité convergente montre que les deux facteurs prédisent la qualité de la relation des joueurs. Enfin, aucune différence n'a été trouvée dans les scores des deux facteurs CEQS associés aux variables sociodémographiques ou socio-sportives. Des recommandations sont présentées sur l'utilisation et l'interprétation de cet instrument par des experts en psychologie du sport, des entraîneurs et des administrateurs sportifs, et la contribution de la mise en œuvre du CEQS à l'amélioration de l'efficacité dans les sports d'équipe.

São examinadas a estrutura fatorial, as propriedades psicométricas e as normas de interpretação e correção do perfil, e a tipologia da adaptação ao espanhol do Questionário de Eficácia Coletiva para o Esporte (CEQS) de Martínez, Guillén & Feltz (2011), em um amostra de atletas colombianos, porque em suas validações anteriores nenhuma estratégia foi aplicada para minimizar o viés de indeterminação fatorial, confirmatória e por capitalização sobre o acaso. Ao contrário da estrutura de cinco fatores do CEQS originalmente postulada por Martínez et al. (2011), os achados deste estudo mostram uma estrutura de dois fatores. A validade convergente mostra que os dois fatores predizem a qualidade do relacionamento dos jogadores. Por fim, não foram encontradas diferenças nas pontuações dos dois fatores do CEQS associados a variáveis sociodemográficas ou sócio-desportivas. São apresentadas recomendações sobre o uso e interpretação deste instrumento por especialistas em psicologia do esporte, treinadores e administradores esportivos, e a contribuição da implementação do CEQS para a melhoria da eficácia em esportes coletivos.
Profile and Typology of the Collective Efficacy Questionnaire for Sport (CEQS) in Colombia
Profil et typologie du questionnaire d'efficacité collective pour le sport (CEQS) en Colombie
Keywords: Collective efficacy; Sports; Profile; Typology; Eficacia colectiva; Deporte; Perfil; Tipología; Efficacité collective; Sport; Profil; Typologie; Eficácia coletiva; Esporte; Perfil; Tipologia; https://purl.org/pe-repo/ocde/ford#5.01.00